Translating One Health knowledge across different institutional and political contexts in Europe - Sarah Humboldt-Dachroeden (BMC, 2023)
Abstract Background Implementing a One Health approach is complex. It demands engaging different sectors and actors in the promotion and protection of human, animal and environmental health. A key challenge for successfully implementing the One Health approach are knowledge translation processes among scientists and policy-makers. Methods An online survey reached 104 experts from 23 European countries, working at national agencies or institutes, universities, ministries, non-governmental organisations (World Health Organization, World Organisation for Animal Health), and European Union (EU) agencies. Qualitative and quantitative analyses were conducted to describe experts' perceptions. Results This study indicated a lack of networks among scientists and between scientists and policy-makers. Relations of scientists and policy-makers were perceived as challenging due to different interests and priorities, leading to difficulties in reaching political attention for One Health topics. It also highlighted a favoured attention to some One Health topics (e.g. antimicrobial resistance) as opposed to others (e.g. environmental issues). Important international actors to push One Health policies forward were the Quadripartite organisations and EU agencies. National actors (government agencies, national research institutes, universities) were on average perceived to be more important than international actors due to their roles and influences. Factors influencing the knowledge translation process were the different languages spoken by scientists as well as politicians, and an equivocal understanding of the One Health approach. Conclusion The study shows the importance of leadership to establish interdisciplinary networks and to problematise One Health issues with clear scope and targets. This will help to link knowledge to needs and capabilities of policy-makers. Establishing strong relationships among national and international actors can encourage networks and raise awareness of the One Health approach to policy-makers. Lastly, promoting research communication skills of scientists can provide a valuable tool to reach policy-makers to enhance attention to One Health topics.